Technology implementation barriers in the Malaysian herbal industry: A case study - Nordin, Noraini; Othman, Siti Norezam; Che Mat, Ruzinoor (Penerbit Universiti Utara Malaysia, 2008)
Technology is an essential component in all types of organisations and most organisations have reasons to implement new technology. The most fundamental justification for new technology implementation is that the technology must be able to contribute to strong competitive advantages and also increase or create long-term profit. In most small and medium enterprises (SMEs), there are barriers or obstacles in implementing these technologies. This article report a study aimed in investigating barriers faced by the Malaysian herbal industry in implementing technologies in their factory. Most of the local herbal manufacturing firms are categorised as SMEs which are usually considered to be lagged behind larger companies in technology usage. As this was an exploratory research, a case study method was used as it gave in-depth explanation of the main barriers of technology implementation. The results suggested that the main constraint in implementing technologies are lack of technical specialists and financial, aid commitment from top management, low wage rate, and future demand uncertainties.